2001
DOI: 10.1046/j.1365-2141.2001.02817.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disseminated intravascular coagulation after surgery for abdominal aortic aneurysm: clinical and haemostatic response to dalteparin

Abstract: Summary.A 77-year-old man developed chronic disseminated intravascular coagulation (DIC) after surgical repair of a large infrarenal aortic aneurysm. Selfadministered subcutaneous dalteparin therapy (5000 units o.d.) led to rapid relief of symptoms and sustained improvements in his platelet count and fibrinogen level; activation of coagulation and fibrinolysis appeared to be relatively unaffected. Long-term treatment with lowmolecular-weight heparin can provide good symptomatic control of chronic DIC associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
12
0
1
Order By: Relevance
“…The first such reported case was treated successfully with enoxaparin 4000 U daily 4 and in another report dalteparin 5000 U daily was effective. 7 Both these patients responded to a thromboprophylactic dose of LMWH. The currently discussed patient showed only partial response to dalteparin 5000 U daily but responded well to a dose of 10 000 U daily.…”
Section: Discussionmentioning
confidence: 98%
“…The first such reported case was treated successfully with enoxaparin 4000 U daily 4 and in another report dalteparin 5000 U daily was effective. 7 Both these patients responded to a thromboprophylactic dose of LMWH. The currently discussed patient showed only partial response to dalteparin 5000 U daily but responded well to a dose of 10 000 U daily.…”
Section: Discussionmentioning
confidence: 98%
“…Palmaz stenting and periaortic ligatures are feasible techniques for the treatment of proximal endoleaks, although the perioperative mortality of periaortic ligatures is higher compared with other less invasive techniques. 12 Cummins et al 13 showed that long-term treatment with low-molecular-weight heparin (dalteparin) in a patient with an aortic dissection who was unfit for open surgery provided symptomatic control of chronic DIC.…”
Section: Discussionmentioning
confidence: 98%
“…In patients with DIC, local activation of coagulation results in the systemic depletion of coagulation factors and platelets, 1 and the basic principal for treating DIC is anticoagulation therapy, such as heparin. 7,8,11,12 Cummins et al reported that long-term treatment with LMWH could provide good symptomatic control of chronic DIC associated with AAA, 5 and as far as we could ascertain, there is not a great difference between LMWH and UFH. However, subcutaneous injection was ruled out because of the large purpura at the site of injection and so we needed to use a drug that could be administered as a bolus injection.…”
Section: Discussionmentioning
confidence: 99%
“…9 Clinical hemorrhagic diathesis accompanying aortic aneurysms was first reported in 1971 15 and is now well recognized. 5,7,16 The activation of coagulation in such cases may be caused by tissue factor from subendothelial elements. In a previous study, we reported that the degree to which the fibrinolytic system is activated varies according to the underlying disease responsible for DIC and we have named the condition involving a markedly enhanced fibrinolytic system as "fibrinolysis dominant DIC".…”
Section: Discussionmentioning
confidence: 99%